Menstrual Patterns of Progestin Injection Contraception and Combinations in Kisaran Barat District - Ira Puspita; Nur Afi Darti (Talenta Publisher, 2019)
The increase in population and the high maternity death rate has caused the government to mitigate birth rate by providing KB (Family Planning), using contraceptive devices; one of them is progesterone and estrogen hormone injection, done by intramuscularly method in fertility-aged women. Its side-effect isthat it can influence menstruation irregularity. The objective of the research was to find out menstruation pattern of the users of progestin and combination injections at Kelurahan Sendang Sari and Kelurahan Dadi Mulyo, Kisaran Barat Sub-district, where the research was done. The population was 348 people at the two villages, and 76 of them were used as the samples, taken by using accidental sampling technique. The result of the research showed that 32 respondents (84.2%) were not in abnormal category in their menstruation pattern, using progestin injection, and 29 respondents (76.3%) were in abnormal category in the menstruation pattern, using combination injection. It is recommended that KB counselors provide counseling about the mechanism of the work of injection contraception which causes side-effect of menstruation irregularity.